تأثير العلاقة بين تكنولوجيا المعلومات والعدالة التنظيمية في تعزيز الريادة الاستراتيجية: دراسة تحليلية لآراء عينة من مديري شركة آسيا سيل في إقليم كوردستان العراق - عبدالله، مهابات نوري; اومر، شيروان عمر; صادق، زانا مجيد (جامعة صلاح الدين, 2020)
يهدف البحث إلى إيجاد العلاقة بين تكنولوجيا المعلومات بمكوناتها (الأجهزة، شبكات الاتصال، البرامجيات، قاعدة المعلومات)، والعدالة التنظيمية بأنواعها (العدالة التوزيعية، العدالة الإجرائية، العدالة التفاعلية، العدالة التقييمية)، وتحديد تأثير هذه العلاقة في تعزيز الريادة الاستراتيجية أبعادها (القدرات الإبداعية، تحمل المخاطر، اغتنام الفرص، الثقافة الريادية). ولتحقيق أهداف البحث، تم تصميم استمارة الاستبانة شملت (60) فقرة وتم اختيار شركة آسيا سيل للاتصالات في إقليم كوردستان كميداناً للبحث، ومثلت عينة البحث مجتمعها والمتمثلة بـ (93) مديراً، وتم توزيع (93) استمارة الاستبانة وأعيدت (91) استمارة وتم استبعاد (4) استمارة لعدم صلاحيتها للتحليل وبذلك تبقى (87) الاستمارة صالحة للتحليل، وبلغت نسبة الاسترجاع إلى (93.54%)، وفي ضوء ذلك جرى جمع وتحليل البيانات واختبار الفرضيات باستخدام الحزمة الإحصائية للعلوم الاجتماعية (spss)، ومن أبرز الاستنتاجات التي وصل إليه البحث هي: وجود تأثير معنوي للعلاقة بين المتغيرين المستقلين والمتغير التابع، وأوصى البحث بضرورة العمل على رفع مستويات تكنولوجيا المعلومات للشركة المبحوثة والعمل على التعامل مع الكوادر الوظيفية بشكل عادل من حيث الحوافز والرواتب التشجيعية التي تساهم في تعزيز الريادة الاستراتيجية.
The research aims to find the relationship between information technology with its components (hardware, communication networks, software, and database), organizational justice of all kinds (distributive justice, procedural justice, interactive justice, evaluation justice), and determine the impact of this relationship in enhancing strategic leadership dimensions (creative capabilities), Take risks, seize opportunities, entrepreneurial culture). In order to achieve the objectives of the research, the questionnaire was designed to include (60) paragraphs. The research sample represented its community (93) managers and (93) questionnaire forms were distributed and returned. (91) Questionnaire was excluded (4) form for invalidity of the analysis and thus remain (87) form valid for analysis, and the rate of retrieval to (93.54%). In light of this, data were collected and analyzed and hypotheses were tested using SPSS. Asiacell Telecom was selected in Kurdistan Region as a field of research. Among the most important conclusions reached by the research are: the existence of a significant impact of the relationship between the independent variables and the dependent variable, the research recommended the need to work to raise the levels of information technology for the company interviewed and work to deal with the cadres in a fair manner in terms of incentives and salaries that contribute to the promotion of strategic leadership. interviewed and work to deal with the cadres in a fair manner in terms of incentives and salaries that contribute to the promotion of strategic leadership.
Keywords: تكنولوجيا المعلومات -- العدالة التنظيمية -- الريادة الاستراتيجية -- القدرات الإبداعية -- إقليم كوردستان -- العراق